The Impact of School Operational Assistance Funds on Students’ Performance in Jakarta - Ferry Doringin; Stepanus Silaban; Theodorus Pangalila; Karla Sasia (Technium Social Sciences Journal, 2023)
This study explores the impact of School Operational Assistance (BOS) funds on school performance in DKI Jakarta province, Indonesia. The research focuses on schools ranked in the top 1000 in the Computer Based Writing Examination (UTBK) in 2021 and 2022. BOS funds are distributed by the Ministry of Education and Culture to provide non-personnel costs for educational units and are expected to enhance the quality of education. Using correlation analysis, the study found that in 2021, there was no significant difference in school performance between schools that received or did not receive BOS funds. However, in 2022, the research reveals that the number of students who received BOS funds can predict the UTBK score, indicating that BOS funds do impact school performance. The study concludes that the distribution of BOS funds has a positive impact on school quality, but it requires accountability, transparency, stakeholder involvement, and clarity of rules to be successful.